2019
DOI: 10.1002/cam4.2459
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged postoperative ileus in gastric surgery: Is there any difference between laparoscopic and open surgery?

Abstract: Background Prolonged postoperative ileus (PPOI) is a common complication after abdominal surgery, but data about risk factors of PPOI for patients with gastric cancer are rare. We sought to investigate the impact of laparoscopic versus open surgery for PPOI after gastric cancer surgery. Methods A retrospective cohort study was conducted using a registry database consecutively collected from June 2016 to March 2017. PPOI was defined as no bowel function persisting for more than 4 days. Univariate analysis and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…7,8 The average estimated blood loss of the laparoscopic approach was universally lower open approach, but warm ischemia time (WIT) was longer. 9,10 In a matched-pair study, the renal function was poorer in the laparoscopic PN cohort in the shortterm after surgery. 11 There is no difference in PFS or OS between laparoscopic PN (LPN) and open PN (OPN) with laparoscopic expertise.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The average estimated blood loss of the laparoscopic approach was universally lower open approach, but warm ischemia time (WIT) was longer. 9,10 In a matched-pair study, the renal function was poorer in the laparoscopic PN cohort in the shortterm after surgery. 11 There is no difference in PFS or OS between laparoscopic PN (LPN) and open PN (OPN) with laparoscopic expertise.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with open colectomy, laparoscopic colectomy has many advantages, such as faster postoperative return of bowel function, fewer complications, less pain, fewer hospital stays, and similar long-term effect [ 16 18 ]. The clinical practice guideline for enhanced recovery after colon and rectal surgery from the ASCRS and SAGES strongly recommends employing a minimally invasive surgical approach whenever expertise is available and appropriate for colon cancer [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second most common reason for noncompliance was postoperative ileus (n = 111, 11.0%). Liang et al [ 18 ] reported that the proportion of patients with ileus after laparoscopic gastrectomy was 14.14%. Huang et al [ 19 ] reported ileus after laparoscopic gastrectomy in 18.52% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is expected that the inflammatory response or decreased intestinal motility after surgery is more severe. These factors are thought to increase the likelihood of noncompliance [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%